Emerging phenotypes of sarcoidosis based on 18F-FDG PET/CT: a hierarchical cluster analysis. (1st February 2020) - Papiris, Spyros A; Georgakopoulos, Alexandros; Papaioannou, Andriana I; Pianou, Nikoletta; Kallergi, Maria; Kelekis, Nikolaos L.; Gialafos, Helias; Manali, Effrosyni D; Chatziioannou, Sofia
ABSTRACT: Objectives : In sarcoidosis, the definition of organ involvement with traditional means appears laborious and somewhat controversial, and phenotyping by the above overlapping. 18 F-FDG PET/CT defines disease extent by activity more precisely, and may result in a better understanding of sarcoidosis disease behavior and phenotypes expression. We hypothesized that 18 F-FDG PET/CT could add in the phenotyping of sarcoidosis patients by unveiling in detail sites of involvement even in clinically and physiologically silent disease. Methods : This study was designed to investigate the role of 18 F-FDG PET/CT in phenotyping sarcoidosis using cluster analysis by adding this new means in the routine work-up of 195 s arcoidosis patients of a single academic center. Results : 18 F-FDG PET/CT succeeded to identify despite the random distribution of the disease, an ordered stratification into 4 phenotypes: I) thoracic nodal hilar-mediastinal, II) thoracic nodal hilar-mediastinal and lungs, III) an extended thoracic and extra-thoracic only nodal phenotype including inguinal-abdominal-supraclavicular stations, and IV) all the above plus systemic organs and tissues such as muscles-bones-spleen and skin. Conclusion : Though further studies are necessary to confirm findings as patterns of disease behavior; the proposed phenotypes may prove useful in the design of future studies with homogeneous cohorts facilitating in sarcoidosis patients a personalized medicine approach.